The acquisition of phonology in a dynamical model of human information processing: a preliminary account - Puppel, Stanisław (Wydawcnictwo Naukowe UAM, 1993)
The problem of the acquisition of first language phonology is dealt with within the general information-processing perspective. In this sense, language acquisition is viewed as a process of biologically founded pattern formation due to information exchanges between an adult and a child. Moreover, the process is cognitive in that the child, as a goal-seeking and error correcting individual, undertakes an intricate task of compressing a huge variety of linguistic stimuli in order to build an effective information code. It is further assumed that the basic mechanism which leads to the establishment of fully articulate linguistic ability is that of simulation. The mechanism works through a compression of a set of initial variables (i.e. initial conditions) into a minimum length algorithm and a subsequent construction of an integrated system of language-specific attractors. It is only then that the language user is capable of participating in an information transaction in a fully developed manner.